Venture Gestation Paths of Nascent Entrepreneurs: Exploring the Temporal Pattern - Liao, Jianwen (Institutional Knowledge at Singapore Management University, 2005)
The venture creation process is often depicted as a linear process composed of sequential steps. The prescriptive literature often refers to a sequence of events or activities that entrepreneurs would engage. There have been occasional acknowledgements in the literature that the process might be nonlinear as the linear depiction of gestation does not accord with anecdotal accounts from entrepreneurs. However, there has been little empirical research conducted on the venture creation process. This study took a grounded theorizing approach to explore the temporal patterns of venture creation process, and used data mining to analyze a data set of 668 nascent entrepreneurs. Our results suggest that firm gestation is a complex, nonlinear process, in which the developmental stages are hardly identifiable. We also found that firm gestation appears to be a time-based pacing process in which entrepreneurs exploring various possible paths and activities. Complexity theory is applied to explain our findings. Implications and future research directions are provided.